2020
DOI: 10.1038/s41598-020-62293-4
|View full text |Cite
|
Sign up to set email alerts
|

The HSP90 inhibitor Onalespib exerts synergistic anti-cancer effects when combined with radiotherapy: an in vitro and in vivo approach

Abstract: Oncogenic client-proteins of the chaperone Heat shock protein 90 (HSP90) insure unlimited tumor growth and are involved in resistance to chemo-and radiotherapy. The HSP90 inhibitor Onalespib initiates the degradation of oncoproteins, and might also act as a radiosensitizer. The aim of this study was therefore to evaluate the efficacy of Onalespib in combination with external beam radiotherapy in an in vitro and in vivo approach. Onalespib downregulated client proteins, lead to increased apoptosis and caused DN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 31 publications
1
18
0
1
Order By: Relevance
“…Mechanistically, our results together with prior reports reveal that HSP90i-mediated apoptosis induction upon ionizing irradiation derives from targeted disintegration of crucial DNA damage response regulators and is executed via the intrinsic apoptosis pathway as indicated by its clear dependence on functional Bax (37,39). The observed accelerated transit into secondary necrosis interestingly was dependent on hyperactive Kras.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Mechanistically, our results together with prior reports reveal that HSP90i-mediated apoptosis induction upon ionizing irradiation derives from targeted disintegration of crucial DNA damage response regulators and is executed via the intrinsic apoptosis pathway as indicated by its clear dependence on functional Bax (37,39). The observed accelerated transit into secondary necrosis interestingly was dependent on hyperactive Kras.…”
Section: Discussionsupporting
confidence: 78%
“…Furthermore, HSP90 in tumor cells is largely organized in multi-chaperone complexes which exhibit higher affinity for HSP90i than "normal" HSP90 complexes in non-malignant cells, thus ensuring a relevant degree of tumor specificity for HSP90i-based targeted radiosensitization (68). In this context, we and others have previously shown the synergistic therapeutic efficacy of HSP90 inhibition in combination with radiotherapy in different models of CRC in vitro and in vivo (34,37,39).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Among them, onalespib (AT13387) is a potent second-generation compound, currently undergoing phase II studies in advanced solid tumors ( 13 , 17 ). Studies have demonstrated potent radiosensitizing effects of onalespib both in vitr o and in vivo , an effect likely mediated by impairment of the DNA damage response ( 13 , 21 , 22 ). Here, combination therapy of onalespib and radiotherapy resulted in a substantial increase in DNA double breaks (DSBs) as well as delay in DNA repair measured by the DSB markers γH2AX and 53BP1 ( 22 ).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have demonstrated potent radiosensitizing effects of onalespib both in vitr o and in vivo , an effect likely mediated by impairment of the DNA damage response ( 13 , 21 , 22 ). Here, combination therapy of onalespib and radiotherapy resulted in a substantial increase in DNA double breaks (DSBs) as well as delay in DNA repair measured by the DSB markers γH2AX and 53BP1 ( 22 ). These findings raise the question whether HSP90 inhibition may also enhance the cytotoxic effect of cisplatin, due to similarities between the effects of cisplatin and ionizing radiation on tumor cells.…”
Section: Introductionmentioning
confidence: 99%